2021
DOI: 10.3389/fpsyg.2021.670824
|View full text |Cite
|
Sign up to set email alerts
|

Changes in and Effects of Foreign Language Classroom Anxiety and Listening Anxiety on Chinese Undergraduate Students’ English Proficiency in the COVID-19 Context

Abstract: The present longitudinal survey study explored changes in and effects of foreign language classroom anxiety (FLCA) and listening anxiety (FLLA) on Chinese undergraduate students’ English proficiency over a semester in the COVID-19 context. A set of 182 matching questionnaires was collected from first-year undergraduate English as a foreign language learners at two time points of a 16-week semester. Analyses of the data revealed the following major findings: (1) the participants experienced high levels of FLCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 62 publications
3
37
0
Order By: Relevance
“…Analyses of the data revealed that both the experimental and control groups outperformed in post-test oral presentations and move structures and became significantly less anxious about speaking English after the experiment, with a large effect size. Consistent with those found in many studies on anxiety in SL/FL contexts (Alcòn-Soler, 2015;Ataiefar & Sadighi, 2017;Grant et al, 2018;Hsiao et al, 2017;Lindgren et al, 2016;Liu, 2021;Liu & Yuan, 2021;Moeller & Catalano, 2015), these findings further confirm the belief that increased exposure and practice help improve speaking performance and reduce anxiety.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Analyses of the data revealed that both the experimental and control groups outperformed in post-test oral presentations and move structures and became significantly less anxious about speaking English after the experiment, with a large effect size. Consistent with those found in many studies on anxiety in SL/FL contexts (Alcòn-Soler, 2015;Ataiefar & Sadighi, 2017;Grant et al, 2018;Hsiao et al, 2017;Lindgren et al, 2016;Liu, 2021;Liu & Yuan, 2021;Moeller & Catalano, 2015), these findings further confirm the belief that increased exposure and practice help improve speaking performance and reduce anxiety.…”
Section: Discussionsupporting
confidence: 89%
“…The use of these instruments has generated a plethora of empirical research in various SL/FL contexts on anxiety related to SL/FL listening, speaking, reading, and writing (Botes et al, 2020;Dewaele & Al Saraj, 2015;Dewaele & Alfawzan, 2018;Horwitz, 2016;Liu, 2018Liu, , 2021Liu & Jackson, 2008;Liu & Xiangming, 2019;Liu & Yuan, 2021;MacIntye, 2017;Serraj & Nordin, 2013;Shirvan & Taherian, 2021;Zhou, 2017). These studies have consistently shown that FLA is largely negatively correlated with SL/FL learning outcomes although it has sometimes been shown to be facilitating.…”
Section: Literature Review Foreign Language Speaking Anxietymentioning
confidence: 99%
“…Facing this unexpected learning context, EMI students may encounter difficulties and challenges they have seldom had before, such as technology-provoked anxiety (Bryson & Andres, 2020;Kaisar & Chowdhury, 2020;Valizadeh, 2021). Liu and Yuan (2021) showed that online learning environments strongly influence the anxieties of EMI students and directly affect their speaking proficiency. Moreover, Valizadeh (2021) found that most EMI students in the university felt more anxious in online classrooms due to individual differences and preferences, lack of technological knowledge, and technical difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…First, the literature is saturated with studies demonstrating the bivariate relationship among skill-based anxieties and between the FLCAS and a language skill. For instance, Liu and Yuan (2021) have recently found a high positive correlation between FLCA and listening anxiety. Moreover, in their mediation analysis examining the effect of some other variables, Chow et al (2018) revealed a significant correlation between reading and listening anxiety.…”
Section: Discussionmentioning
confidence: 99%